Constructing National Ideology and Values: A Comparative Study of Southeast Asian and Southern African Inaugural Speeches By Leaders in English Using Thematic Analysis - Hidayati, Salila Prasidya (Jurnal Indonesia Sosial Sains, 2025)
This study examines how modern national leaders use inaugural speeches to shape national ideology and express shared values. These speeches, often delivered during crucial political transitions, serve as rhetorical frameworks where leaders communicate their vision, moral stance, and governing philosophy to both domestic and international audiences. Focusing on four English-language inaugural addresses from Southeast Asia (the Philippines and Singapore) and Southern Africa (South Africa and Zambia), this research applies comparative thematic analysis to identify common and contrasting ideological patterns in postcolonial and developmental-state contexts. Using Braun and Clarke’s (2006) six-phase model, the study identifies and interprets recurring themes that show how leaders employ language to establish legitimacy, unity, and moral authority. Reliability was confirmed using Cohen’s Kappa (κ = 0.851), indicating a high level of analytical consistency. Findings reveal that while all leaders use optimistic, future-oriented rhetoric emphasizing progress and inclusivity, their underlying value systems differ. Southeast Asian leaders tend to focus on pragmatic governance, economic development, and institutional continuity, whereas Southern African leaders center their messages on moral renewal, democracy, and resilience, reflecting their nations’ liberation histories. The study contributes to discourse research by showing how political leaders in non-Western contexts use language as a tool for reproducing ideology and shaping collective identity.